(untitled) (Global Journal of Management and Business Research, 2021)
This paper attempts to answer the question Whether the economic growth in India is affected by stability at the Central and States level political stability A Political Stability Index PLSI is constructed using four political stability measures at Central and States level for both the Houses of the Legislatures This index the independent variable is tested on two dependent economic growth variables Per Capita Income and Gross Capital Formation The time for the study is 1981-2017 37 years at India Central level and 1991-2015 25 years at the States level according to the availability of data with a lag period of 1 year as policies bear results the following year The analysis very modestly supports the hypothesis at the Central level However the impact is more robust at the States level evident from continuous governmental stability of many States Principal Component Analysis method is used to construct the index and then Regression Analysis is used to measure the impact on dependent variable